2019
DOI: 10.14507/epaa.27.3793
|View full text |Cite
|
Sign up to set email alerts
|

The Texas special education cap: Exploration into the statewide delay and denial of support to students with disabilities

Abstract: State accountability systems have been a primary school reform initiative in the U.S. for the past twenty years, but often produce unintended negative consequences. In 2004, the Texas Education Agency (TEA) implemented the Performance Based Monitoring and Analysis System (PBMAS) which included an accountability indicator focused on the percentage of students found eligible for special education under the Individuals with Disabilities Education Act (IDEA), the nation’s special education law. From 2004 through 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…She added, "What I'm getting at, what I don't think I was prepared to do at all, was help myself or others look at the data, discuss what we know, and come to a logical and data-driven decision." Three principals noted a statewide problem in special education identification and felt they could have learned more about identification processes (see DeMatthews & Knight, 2019).…”
Section: Content Knowledge and Expertisementioning
confidence: 99%
“…She added, "What I'm getting at, what I don't think I was prepared to do at all, was help myself or others look at the data, discuss what we know, and come to a logical and data-driven decision." Three principals noted a statewide problem in special education identification and felt they could have learned more about identification processes (see DeMatthews & Knight, 2019).…”
Section: Content Knowledge and Expertisementioning
confidence: 99%
“…For each indicator, PBMAS assigned a level of intervention and required actions to school districts (OSEP, 2017). School districts were given scores indicating appropriate performance when the total percentage of their students receiving special education services was 8.5% or lower of the district's total student enrollment (DeMatthews & Knight, 2019).…”
Section: The Texas Special Education Capmentioning
confidence: 99%
“…These contrasts are currently unavailable from the few peer-reviewed studies examining the TSEC (Ballis & Heath, 2021a, 2021b; DeMatthews & Knight, 2019). Instead, the available studies have mostly contrasted students attending schools only within Texas or reported on district- and school-based factors that influenced special education enrollment trends as well as the causal impacts of the TSEC on student achievement, high school completion and college enrollment, post-secondary employment, and later earnings including for students of color.…”
Section: Limitations In the Extant Knowledge Base About The Texas Spe...mentioning
confidence: 99%
“…The monitoring report from the Department of Education found that TEA failed to provide students with disabilities a free, appropriate education and failed to monitor and evaluate students in accordance with IDEA. While the Department of Education report and Houston Chronicle coverage shed light on the extreme actions taken by TEA to reduce special education expenditures, research is just beginning to uncover the array of detrimental outcomes associated with the policy (DeMatthews & Knight, 2019;DeMatthews & Serafini, 2019).…”
Section: Policy and Principal Turnover: The Impact Of The Texas Special Education Capmentioning
confidence: 99%
“…In fact, only a few studies have examined the adverse outcomes related to the Texas special education cap (DeMatthews & Serafini, 2019). However, these studies primarily focus on the students who were denied services (Knight & DeMatthews, 2018;DeMatthews & Knight, 2019).…”
Section: Policy and Principal Turnover: The Impact Of The Texas Special Education Capmentioning
confidence: 99%